PENERAPAN TEKNIK SUPERVISI KELOMPOK DENGAN METODE WORKSHOP UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DI SD NEGERI LAMKLAT TAHUN PELAJARAN 2018/2019 - Ismuha (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2019)
One of the factors determining the success of learning is the teacher's ability in drawing up the planning of learning that is contained in the RPP. In drawing up the plan of implementation of the learning (RPP), required the ability of the teacher in facilitating effective learning experience that is able to strengthen the character of students. The integration of the values of the characters in the learning expected not limited to written administratively, but would later be applied with natural learning. The reality on the ground shows that there are still teachers of elementary school level (SD) in compiling a RPP has not fully refers to the Permendikbud number 22 year 2016 on standard processes, based on the syllabus, basic competency analysis (KD) as well as with pay attention to the principles and steps in crafting a RPP. Based on the identification issue above, the formulation of problems in the research of the action of this school is